Economic Based Divorce from the Maqashid Shariah Perspective: Analysis of the Decision of the North Jakarta Religious Court Judge Number 2102/Pdt.G/2022/PA.JU - Imtah Salsabila Pratiwi; Isman (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to analyze judicial decisions regarding the prevalence of divorce in Indonesia from the perspective of Maqashid Syariah. The study holistically examines the high divorce rate of 23% per year in Indonesia within the framework of Islamic values inherent in Maqashid Syariah. It explores the factors that judges consider when making divorce decisions, including economic, family, and social aspects. Furthermore, the research discusses intervention strategies that can be implemented to enhance family resilience and prevent divorce. Employing a qualitative approach and content analysis, the study thoroughly analyzes the data to achieve a comprehensive understanding of judicial decisions concerning the prevalence of divorce in Indonesia from the perspective of Maqashid Syariah. The findings indicate that judges primarily base their divorce decisions on a legal-formal perspective, thereby contributing to the prevalence of divorce driven by economic reasons. The research also provides recommendations for effective intervention strategies to bolster family resilience.